素養導向教育改革下之中學教師壓力：量表發展與壓力改變之影響因素 Stress Among Secondary School Teachers Under the Standard-Based Educational Reform: Development of Inventories and Factors Influencing Stress Change - 丁毓珊 Yu-Shan Ting; 葉玉珠 Yu-Chu Yeh; 江瑞鈴 Jui-Ling Chiang (National Taiwan Normal University, 2023)
隨著新課綱正式啟動，身為教學現場第一線的中學教師面臨前所未有的挑戰與壓力。本研究旨在分析中學教師當前的壓力程度，以及個人與學校背景因素對中學教師在新課綱實施前後壓力改變之效果。本研究基於「教育專家與專家教師社群」的焦點座談結果，發展適用於中學教師的「溝通與輔導壓力量表」及「課程與教學壓力量表」，並以量表探究中學教師在新課綱實施前後，壓力的變化情形及其影響因素。本研究參與者為205位中學教師。研究結果發現：一、本研究發展的壓力量表均具良好信度與效度；二、教師溝通與輔導壓力量表包含三個因素：親師溝通、同事與師生溝通、學生輔導；三、教師課程與教學壓力量表包含兩個因素：素養導向課程與教學、素養導向自主學習引導；四、在新課綱實施後，國中與高中教師的壓力均顯著提升，但高中教師感受到的壓力轉變幅度高於國中教師；五、性別、教育程度、職務、學校規模對教師壓力轉變沒有效果；六、教師的婚姻狀況與有無小孩、任教階段對中學教師壓力轉變有顯著效果。本研究發展之兩份教師壓力量表，有助於瞭解強調素養導 向教學的教育改革下中學教師之壓力及其影響因素，本研究發現亦提供教育當局在此波教育改革的後續規劃與改善之參考。 The implementation of the 108 Curriculum Guidelines has increased the challenges and stress levels of secondary school teachers. Therefore, this study evaluated the stress levels of teachers and whether personal and school factors influenced changes in stress levels before and after the implementation of the 108 Curriculum Guidelines. Through focus-group discussions on the 108 Curriculum Guidelines, we developed the Inventory of Teacher Stress in Communication and Counseling (ITS-CC) and the Inventory of Teacher Stress in Curriculum and Instruction (ITS-CI). In addition, using the developed inventories, we explored the effects of several personal and school variables on teachers' stress changes. A total of 205 junior and senior high school teachers were recruited as study participants. The main findings are as follows: (1) Both the inventories developed in this study have adequate reliability and validity. (2) The ITS-CC includes three factors: parent-teacher communication, colleague and student communication, and student counseling. (3)The ITS-CI includes two factors: standard-based curriculum and instruction and guidance for self-directed learning. (4) Teachers' marital status, number of children, and the educational stages of teaching significantly affected the teachers' stress changes. Overall, secondary school teachers experienced different types and levels of stress. In conclusion, the inventories developed in this study are valid instruments for understanding teachers' stress and related factors under the current educational reform. Additionally, the study findings can serve as a reference for further improvement of the 108 Curriculum Guidelines. Introduction The implementation of the 108 Curriculum Guidelines has increased the challenges and stress levels of secondary school teachers. These teachers are required not only to respond to the needs of innovation, redesign competency-oriented courses and teaching, and develop self-directed learning courses but also to conduct counseling and communicate with parents about the new curriculum guidelines. Moreover, studies have found that secondary school teachers with different backgrounds experienced different types of stress (e.g., Bottiani et al., 2019; Chen, 2010; Li & Cheng, 2013; Yeh et al., 2017). Therefore, this study investigated the stress levels of secondary school teachers with the implementation of the educational reform. Additionally, this study explored the effects of different demographic variables (including gender, education level, marital status, children, job title, school size, and educational stages of teaching) on the changes in stress levels before and after the educational reform. Literature Review Teaching is an occupation involving high levels of stress. Studies have reported that teachers experience moderate-to-high levels of work stress (Harmsen et al., 2018; Johnson et al., 2005; Näring et al., 2006). Notably, educational reforms may exacerbate such stress and be new sources of stress to teachers (Zhang et al., 2018). Based on the content and educational goals of the educational reform, we categorized the stress experienced by secondary school teachers into two types: curriculum and teaching as well as counseling and communication. The first category includes stress related to teaching progress, curriculum design, learning assessment, and planning of self-directed learning, and the second category includes stress related to interpersonal relationships, parent-teacher communication, and student counseling. Most teacher stress scales have been developed more than 5 years ago and do not include new problems experienced by teachers in the current educational reform. Therefore, in this study, we developed the ITS-CC and the ITS-CI. Many studies have demonstrated that teachers at different school levels experience varied levels of stress (Chen, 2010; Huang, 2015). Compared with teachers in junior high schools, those in senior high school reported a heavier workload caused by offering elective courses, assisting students with academic portfolios, preparing self-directed learning plans (Ministry of Education, 2014), and others. In addition, empirical research indicates that secondary school teachers with different backgrounds experience varying levels of stress, with gender (Bottiani et al., 2019), marital status (Li & Cheng, 2013), work positions (Yeh et al., 2017), and school size (Bai & Lai, 2014) playing crucial roles. Thus, this study analyzed the effects of several personal and school variables on stress changes of secondary school teachers before and after the new educational reform. Method We first invited six expert teachers to participate in focus-group discussions for determining sources of teacher stress from different perspectives. Based on their responses, we developed two preliminary stress inventories. Then, we recruited 205 secondary school teachers to participate in the investigation study. Participants included 56 male teachers (27%) and 146 female teachers (71%); the gender of 3 teachers was confidential (2%). The instruments used for evaluation included the ITS-CC and ITS-CI. The demographic variables included were gender, educational level, marital status, number of children, job title, school size, and the educational stages of teaching. Item analysis, exploratory factor analysis, internal consistency reliability analysis, confirmatory factor analysis, chi-square test, and repeated measures were performed using IBM SPSS Statistics and AMOS for Windows, version 19. This study was approved by the Institutional Review Board of National Chengchi University, Taiwan, and written informed consent was obtained from all participants. Results and Discussion The ITS-CC includes three factors: parent-teacher communication, colleague and student communication, and student counseling. ITS-CI includes two factors: standard-based curriculum and instruction and guidance of self-directed learning. Both the inventories had adequate reliability and validity; the Cronbach's alpha of both inventories was .93. Regarding the stress levels, the results indicated that secondary school teachers experienced a moderate-to-high level of stress, which is consistent with previous findings (Harmsen et al., 2019;Kovess-Masféty et al., 2006; Näring et al., 2006). Additionally, according to the ITS-CI and ITS-CC, teachers' stress levels significantly increased after the implementation of the 108 Curriculum Guidelines. These results are in line with a previous finding that when new curriculum guidelines are implemented, teachers are required to expend more efforts to guide students to become more autonomous learners, pay more attention to students' learning process, and provide more counseling (Qiu, 2017).